Myxoma viral serpin, Serp-1, a unique interceptor of coagulation and innate immune pathways - Viswanathan, Kasinath; Liu, Liying; Vaziri, Sepideh; Dai, Erbin; Richardson, Jakob; Togonu-Bickersteth, Babajide; Vatsya, Pracha; Christov, Alexander; Lucas, Alexandra R. (Thrombosis and Haemostasis, 2006)
Serpins maintain haemostasis through regulation of serine proteinases in the thrombotic and thrombolytic pathways. Viruses encode serpins that can alter thrombotic and thrombolytic responses producing, in some cases, disseminated intravascular coagulation (DIC). However, it has not been precisely defined how viral serpins induce these profound responses. The rabbit myxoma viral serpin, Serp-1 inhibits urokinase- and tissue-type plasminogen activators (uPA and tPA), plasmin and factor Xa in vitro and exhibits remarkable anti-inflammatory activity in various animal models. The effects of Serp-1 on activation of human platelets, endothelial cells, monocytes and T cells that mediate thrombosis and innate immune responses were therefore examined. We found that Serp-1 attenuated platelet and mononuclear cell adhesion to fibronectin and collagen. Serp-1 similarly inhibited monocyte migration into the peritoneum. Serp-1 inhibition of monocyte migration was lost in uPA receptor (uPAR) deficient mice. Serp-1 bound to the plasma membrane surface and altered uPA activation of endothelial cells (p=0.001), thrombin activation of platelets (p=0.021) and phorbol ester activation of endothelial (p=0.047), monocyte (p=0.011) and Jurkat T cells (p=0.012) as measured by intracellular calcium. Modulation of cellular activation was confirmed by membrane fluidity analysis. Microarray analysis of Serp-1 treated endothelial cells revealed alterations in Inositol 1,4,5-triphosphate receptor type II (ITPR2) a calcium-regulating gene. This study demonstrates the unique capacity ofa viral serpin, Serp-1 to modify adhesion, activation, gene expression and calcium homeostasis in a wide range of cells that regulate coagulation and inflammation. Endothelial cells potentially represent a pivotal regulatory point for Serp-1 anti-inflammatory activity.
Keywords: Serpin; adhesion; calcium; membrane fluidity; ITPR2